Teaching spirituality and work: A praxis-based pedagogy. Issue 5 (November 2013) - Trott, David C
The purpose of this article is to present a praxis-based pedagogy in the classroom teaching of spirituality and work to working adult students. The article provides an overview of classroom scholarship that illuminates activities for transformational learning and emphasizes the importance of four key dialogues: self-dialogue, dialogue with co-workers, dialogue with classmates, and dialogue with the teacher. Such dialogues provide a pathway through the challenges of teaching/learning about spirituality and work by making available an open space for meaning-making and critique around spiritual experiences of work. The author's metalogue throughout provides a parallel dialectical structure relating to the core content; a faithful demonstration to walk the talk of praxis.